Studies in honor of Shaul Shaked - Kohlberg, Etan 1943- (The Israel Academy of Sciences and Humanities, 2019)
"The present volume is based on lectures delivered at a symposium organized by the Israel Academy of Sciences and Humanities on the occasion of the eightieth birthday of Professor Shaul Shaked, who became a member of the Academy in 1986"--Page 7
Includes bibliography of S. Shaked, pages 176-194
Keywords: Judaism / Relations / Zoroastrianism / Congresses; Zoroastrianism / Relations / Judaism / Congresses; Jewish magic / History / Congresses; Judeo-Persian language / Congresses; Judaism / Relations / Christianity / Congresses; Christianity and other religions / Judaism / History / Congresses; Iran / Civilization / To 640 / Congresses; Sassanids / Intellectual life / Congresses; Shaked, Shaul / Bibliography; Christianity; Interfaith relations; Jewish magic; Judaism; Judeo-Persian language; Zoroastrianism; Festschriften; History; Festschrift